Key success factors for team integration practice in Malaysian Industrialised Building System (IBS) construction industry - Mohd Nasrun Mohd Nawi; Mohamed Nor Azhari Azman; Wan Nadzri Osman; Kamaruddin Radzuan; Mazri Yaakob (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Industrialised Building System (IBS) has been recognized as synonymous with industrialisation of the construction industry . In Malaysia, the domination of traditional method in IBS project has gained much attention not only from researchers but also construction industry practitioners as the implementation of IBS through traditional approach almoat always led to the rise of construction problems such as increasing project time and cost, redesigning, ineffective supply chain, and others. Fragmentation process in traditional method is not a line with the concept of IBS which is required a high communication and collaboration among the project stakeholders. This study took closer look at current practice of IBS projects in Malaysia, at the need for an integration approach, and at the availability of integrated approaches in IBS projects with the objective of identifying critical success factors for integrated teams in IBS construction projects. The findings from the Focus Group Discussion (FGD) among construction industry stakeholders revealed the main barriers to the IBS adoption in Malaysia’s construction industry to be poor integration among project stakeholders during the planning and design phase. This was due to the domination of the fragmentation concept of the traditional method.